Vitamin E and fatty acid composition of blended palm oils - Azlan, Azrina; Ismail, Amin; Amom, Zulkhairi; Lim, Pei Hong (WFL Publisher, 2009)
Vitamin E content (ppm) (4 tocopherols and 3 tocotrienols without ?-tocotrienol) and fatty acid composition (FAC) of blended unsaturated oils [corn oil (CO), sesame oil (SO) and rice bran oil (RBO)] with palm olein (PO) at 1 to 1 ratio (v/v) were determined using HPLC and GC, respectively. The vitamin E content in blended oils was significantly different (P<0.05) from levels in the native oils that made the blending with values of 348.6±5.6, 452.0±3.2 and 2774.0±6.3 ppm respectively for PO-CO, PO-RBO and PO-SO. In general, blending of unsaturated oils with PO changed SFA, MUFA and PUFA content of the resulting oils in the range of 21-26, 34-37 and 34-41%, respectively that compatible to the NCEP recommendation. Thus, the use of blended unsaturated oils with palm olein could be beneficial and results in nutritionally balanced fatty acid oils, improved omega-6/omega-3 ratio and increased vitamin E level, particularly the tocotrienol. Finally the use of these blended oils may favor overall dietary nutrient adequacy.